Beyond the Black Box Approach to Ethics! Comment on "Expanded HTA: Enhancing Fairness and Legitimacy" - Lars Sandman; Erik Gustavsson (Kerman University of Medical Sciences, 2016)
In the editorial published in this journal, Daniels and colleagues argue that his and Sabin's accountability for reasonableness (A4R) framework should be used to handle ethical issues in the health technology assessment (HTA)-process, especially concerning fairness. In contrast to this suggestion, it is argued that such an approach risks suffering from the irrrelevance or insufficiency they warn against. This is for a number of reasons: lack of comprehensiveness, lack of guidance for how to assess ethical issues within the "black box" of A4R as to issues covered, competence and legitimate arguments and finally seemingly accepting consensus as the final verdict on ethical issues. We argue that the HTA community is already in a position to move beyond this black box approach.